An Empirical Study on the Impact of Energy Poverty on Carbon Intensity of the Construction Industry: Moderating Role of Technological Innovation - Zhang, Jianhua; Liu, Yushan; Saqib, Najia; Waqas Kamran, Hafiz (Frontiers in Environmental Science, 2022)
As a national pillar industry, the carbon emissions generated by the construction industry have received significant attention. As a large developing country, China has unbalanced regional development and imperfect modern energy infrastructure in some regions, leading to a prominent problem of energy poverty in China. Therefore, this paper constructs the index system of energy poverty using panel data of 30 provinces and cities from 2004 to 2016. This paper analyzes the influence of energy poverty on carbon intensity of construction industry, and constructs the influence model of carbon intensity of construction industry. The results show that (1) The carbon intensity of construction industry increases by 1.683 units per unit increase of energy poverty, showing a positive impact(2) Energy consumption structure has a mediating effect on the impact of energy poverty on carbon intensity of construction industry(3) Technology level plays a moderating role in the main effect of energy poverty and carbon intensity in construction industry; The degree of marketization plays a moderating role in the indirect effect of energy consumption structure and carbon intensity of construction industry. These results offered valuable policy recommendations for sustainable industrial growth.